Osteonecrosis of the jaw after dental implant placement. A case report - J.L. Calvo-Guirado; A. Boquete-Castro; J. Guardia; A. Aguilar Sal Vatierra Raya; J.M. Martínez González; G. Gómez-Moreno (Ariesdue, 2014)
Background: In the past few years, the occurrence of an oral lesion, called osteonecrosis of the jaw, has increasingly been reported in patients undergoing treatment with systemic bisphosphonates (BPs); however, few papers dealing with oral biphosphonates related osteonecrosis of the jaws (BRONJ) can be found in the literature. The purpose of the present case was to report an occurrence of BRONJ after implant insertion. Case report: Ten years ago, eight dental implants were inserted in the jaw of a 65-year-old female. After 5 years of treatment with alendronic acid, a breakdown of the oral mucosa covering the implants occurred with a purulent discharge in the left side of the jaw; periapical radiolucency was present around both distal implants. An en-block resection of the alveolar bone including the two implants was performed. Thirthy-five hyperbaric sessions were taken and no signs of recurrence of the lesion were observed after a follow-up of 20 months. Before the new implant insertion, the patient had suspended the treatment with alendronic acid for 6 months. At the interface of one of the implants, a gap was observed between bone and implant. This bone was non vital, and many osteocyte lacunae were empty. Moreover, this bone appeared to be partially demineralized. Conclusion: There is certainly a temporal association between oral BPs use and development of BRONJ, but a correlation does not necessarily mean causation. In patients undergoing oraltreatment, clinicians must be aware of the increased risk of implant failure.